Oncogenic Brain Metazoan Parasite Infection - Angela N. Spurgeon; Marshall C. Cress; Oroszi Gabor; Qing-Qing Ding; Tomoko Tanaka; Douglas C. Miller (Case Reports in Neurological Medicine)
Multiple observations suggest that certain parasitic infections can be oncogenic. Among these, neurocysticercosis is associated with increased risk for gliomas and hematologic malignancies. We report the case of a 71-year-old woman with colocalization of a metazoan parasite, possibly cysticercosis, and a WHO grade IV neuroepithelial tumor with exclusively neuronal differentiation by immunohistochemical stains (immunopositive for synaptophysin, neurofilament protein, and Neu-N and not for GFAP, vimentin, or S100). The colocalization and temporal relationship of these two entities suggest a causal relationship.